1996
DOI: 10.1111/j.1432-1033.1996.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Tuning the Conformation of Bovine Pancreatic Trypsin Inhibitor Studied by Fourier‐Transform Infrared Spectroscopy

Abstract: A hydrostatic pressure of 1 .5 GPa induces changes in the secondary structure of bovine pancreatic tryspin inhibitor (BPTI) as revealed by the analysis of the amide I' band with Fourier-transform infrared (FTIR) spectroscopy in the diamond anvil cell. The features of the secondary structure remain distinct at high pressure suggesting that the protein does not unfold. The fitted percentages of the secondary structure elements during compression and decompression strongly suggest that the pressure-induced change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 53 publications
4
39
0
Order By: Relevance
“…Subsequent MD simulations revealed that changes in the secondary structures between 10 and 15 kbar were observed (60). These changes could be correlated with changes in the secondary structure observed with high-pressure infrared studies (61). Furthermore, no net unfolding of lysozyme was observed at 10 kbar after 210 ps (20).…”
Section: Resultsmentioning
confidence: 89%
“…Subsequent MD simulations revealed that changes in the secondary structures between 10 and 15 kbar were observed (60). These changes could be correlated with changes in the secondary structure observed with high-pressure infrared studies (61). Furthermore, no net unfolding of lysozyme was observed at 10 kbar after 210 ps (20).…”
Section: Resultsmentioning
confidence: 89%
“…The data that bacterial life may still be possible at pressure above 1 GPa [7] came therefore as a surprise. Only very few proteins have been found to be resistant to such high pressures [20][21][22].…”
Section: Protein Stability Phase Diagrammentioning
confidence: 99%
“…However, since proteins are usually studied at low molar concentrations, the role of the solvent is often underestimated. Several reports indicate the crucial role of water in protein unfolding [20,30].…”
Section: Protein Stability Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of proteins irreversibly denature at pressures of a few kbar, there are numerous examples of proteins that maintain their structures at well over 10 kbar of pressure. 3–4 Likewise, barophilic organisms have been collected in even the deepest parts of the ocean and below the ocean floor, and many microbes are capable of surviving and growing at pressures of over 10 kbar. 5 As more research is done on deep sea environments it is becoming clear that barophilic organisms may be the rule rather than the exception, and that life may exist and even thrive far below even the deepest parts of the ocean.…”
Section: Introductionmentioning
confidence: 99%